The expression of matrix metalloproteinase-13 (MMP-13) on xenograft and PRF in bone regeneration - Augustina, Eka Fitria; Rivai, Nur Riflianty; Gifary, Haykal Miftah (Brazilian Dental Science, 2023)
Objective: inflammation may play a role in bone loss by altering the bone remodelling process, favouring boneresorption by osteoclasts over bone synthesis by osteoblasts. Matrix metalloproteinase 13 (MMP-13) has the abilityto activate osteoclasts, leading to bone resorption. Regenerative treatments have been widely used in periodontology.When combined with Platelet-rich fibrin (PRF), xenografts will give better results in bone regeneration. The aim ofthis study was to evaluate the effect of xenograft combined with PRF on MMP-13 expression in a bone defect usingan experimentally created bone defect. Material and Methods: eighteen New Zealand rabbits were assigned to threegroups. Each group consisted of six New Zealand rabbits. A critical bone defect with a diameter size of 5 mm wascreated in the right tibia of each rabbit in group 1 (application: xenograft), group 2 (application: PRF), and group 3(application: xenograft and PRF). The PRF was produced from 5 ml of blood taken from each rabbit’s ears. After 30 days,the rabbits were euthanized. The tissue samples were evaluated by immunohistochemical staining. Results: group 3showed the lowest mean expression of MMP-13 (4.50) compared to group 1 (20.50) and group 2 (11.70). Group 3showed a significant difference in the MMP-13 expression compared to group 1 and group 2 (P = 0.000) (P < 0.05).Conclusion: this research showed that the combination of xenograft and PRF had the lowest expression of MMP-13.The application of a xenograft and PRF has better osteogenesis ability in bone regeneration.KEYWORDSMMP-13; Xenograft; Platelet-rich fibrin; Bone regeneration; Inflammation.